Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.analchem.2c01001
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Iron Anchored on 2-D Graphene Carbon to Realize Bridge-Adsorption of O–O as Biomimetic Enzyme for Remarkably Sensitive Electrochemical Detection of H2O2

Abstract: Single-atom catalysis is mainly focused on its dispersed high-density catalytic sites, but delicate designs to realize a unique catalysis mechanism in terms of target reactions have been much less investigated. Herein an iron single atomic site catalyst anchored on 2-D N-doping graphene (Fe-SASC/G) was synthesized and further employed as a biomimetic sensor to electrochemically detect hydrogen peroxide, showing an extremely high sensitivity of 3214.28 μA mM–1 cm–2, which is much higher than that (6.5 μA mM–1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Zhu et al designed an Fe 3 C@C/Fe–N–C material with single atomic sites that exhibits excellent POD-like activity and electrochemical H 2 O 2 sensing ability with a high sensitivity and low detection limit, which can sensitively monitor the H 2 O 2 released from living cells . Li et al reported a biomimetic sensor based on iron single-atom materials to electrochemically monitor H 2 O 2 , which is currently ranked as the best Fe-based catalyst in terms of sensitivity and successful in situ monitoring of the H 2 O 2 released from A549 living cells . Although single-atom nanomaterials for H 2 O 2 monitoring have been constructed, to the best of our knowledge, a flexible and stretchable H 2 O 2 sensor based on single-atom materials has not yet been explored, restricting the application in monitoring ROS in cellular mechanotransduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al designed an Fe 3 C@C/Fe–N–C material with single atomic sites that exhibits excellent POD-like activity and electrochemical H 2 O 2 sensing ability with a high sensitivity and low detection limit, which can sensitively monitor the H 2 O 2 released from living cells . Li et al reported a biomimetic sensor based on iron single-atom materials to electrochemically monitor H 2 O 2 , which is currently ranked as the best Fe-based catalyst in terms of sensitivity and successful in situ monitoring of the H 2 O 2 released from A549 living cells . Although single-atom nanomaterials for H 2 O 2 monitoring have been constructed, to the best of our knowledge, a flexible and stretchable H 2 O 2 sensor based on single-atom materials has not yet been explored, restricting the application in monitoring ROS in cellular mechanotransduction.…”
Section: Introductionmentioning
confidence: 99%
“…32 Li et al reported a biomimetic sensor based on iron single-atom materials to electrochemically monitor H 2 O 2 , which is currently ranked as the best Fe-based catalyst in terms of sensitivity and successful in situ monitoring of the H 2 O 2 released from A549 living cells. 33 Although single-atom nanomaterials for H 2 O 2 monitoring have been constructed, to the best of our knowledge, a flexible and stretchable H 2 O 2 sensor based on single-atom materials has not yet been explored, restricting the application in monitoring ROS in cellular mechanotransduction. In addition, the design and fabrication of high-performance electrocatalysts where the H 2 O 2 reduction reaction (HPRR) occurs before the oxygen reduction reaction (ORR) are essential because hypoxia usually leads to oxidative stress and the production of ROS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16a and b). 167 DFT calculation exhibits that the distances between neighbouring sites match the optimum “bridge-adsorption” mode for the catalysis.…”
Section: Sensing Applications Of Sacsmentioning
confidence: 94%
“…Li et al prepared FeSAs (NH 2 -UIO-66 NPs) by coordinating Zr66 clusters with 2-amino-terephthalic acid and developed a H 2 O 2 sensor with a low detection limit. Li et al synthesized FeSAs anchored to two-dimensional nitrogen-doped graphene to detect H 2 O 2 secretion from A549 cells. Therefore, by changing the synthesis mechanism of FeSAs, it is expected to develop H 2 O 2 detection sensors with broad application prospects.…”
Section: Introductionmentioning
confidence: 99%